2015
DOI: 10.1073/pnas.1512991112
|View full text |Cite
|
Sign up to set email alerts
|

Dystrophin–glycoprotein complex regulates muscle nitric oxide production through mechanoregulation of AMPK signaling

Abstract: Patients deficient in dystrophin, a protein that links the cytoskeleton to the extracellular matrix via the dystrophin-glycoprotein complex (DGC), exhibit muscular dystrophy, cardiomyopathy, and impaired muscle nitric oxide (NO) production. We used live-cell NO imaging and in vitro cyclic stretch of isolated adult mouse cardiomyocytes as a model system to investigate if and how the DGC directly regulates the mechanical activation of muscle NO signaling. Acute activation of NO synthesis by mechanical stretch wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 63 publications
(82 reference statements)
1
66
0
4
Order By: Relevance
“…; Hurt et al . ; Garbincius & Michele, ). We quantified the pnNOS level using a phospho‐S1412‐nNOS‐specific antibody by western blot.…”
Section: Discussionmentioning
confidence: 99%
“…; Hurt et al . ; Garbincius & Michele, ). We quantified the pnNOS level using a phospho‐S1412‐nNOS‐specific antibody by western blot.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, recent investigations have revealed that pharmacological AMPK activation promotes translocation of the Na + /K + ‐ATPase a 1 subunit to the sarco‐lemma and increases activity of the ion pump (35). Furthermore, Garbincius and Michele (37) demonstrated that stretch‐induced production of NO in cardiomyocytes was dependent on AMPK signaling after mechano‐transduction from the DAPC. Thus, our findings support the concept that AMPK may be an important component of the structure and function of the sarcolemmal compartment.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, chronic pharmacological AMPK stimulation increases DAPC expression in skeletal muscle (11). Moreover, the presence and function of the kinase at the sarcolemma has been recently established (35, 37, 51). Based on this evidence, we hypothesized that removal of muscle AMPK would decrease DAPC gene expression and by extension would reduce its membrane localization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DAPC is thought to primarily serve a mechanical role, functioning as a physical link between the internal cytoskeleton and extracellular matrix (ECM) 4, 5 , though roles in mediating signaling are emerging 6, 7 . In DMD, loss of functional dystrophin and the consequential loss of the DAPC enhances sarcolemma susceptibility to contraction-induced damage resulting in repetitive cycles of muscle degeneration and regeneration 8 .…”
Section: Introductionmentioning
confidence: 99%